2017
DOI: 10.3892/or.2017.5583
|View full text |Cite
|
Sign up to set email alerts
|

CD24 expression is a marker for predicting clinical outcome and regulates the epithelial-mesenchymal transition in ovarian cancer via both the Akt and ERK pathways

Abstract: The degree of peritoneal dissemination and chemotherapy-resistant tumors is related to the prognosis in patients with advanced-stage ovarian cancer. The epithelial-mesenchymal-transition (EMT) is a multifaceted pathological program that endows cancer cells with the ability to invade and disseminate. CD24 is frequently overexpressed in various human cancers and is correlated with a poor prognosis. We herein examined the functions of CD24 in human ovarian cancer cell lines and evaluated how it contributes to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 40 publications
4
79
0
2
Order By: Relevance
“…Ischemic cerebrovascular disease (ICD) refers to a group of clinical syndromes arising from cerebral circulatory dysfunction of various causes, and brain damage and neurological dysfunction of patients caused by cerebral ischemia, hypoxia and necrosis at the associated blood vessel zone (1). The incidence rate of ICD among cerebrovascular diseases is ~70% in China (2). It has a serious effect on the health and life of patients, is a burden to the family and society, and inflicts substantial social and economic costs (3).…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic cerebrovascular disease (ICD) refers to a group of clinical syndromes arising from cerebral circulatory dysfunction of various causes, and brain damage and neurological dysfunction of patients caused by cerebral ischemia, hypoxia and necrosis at the associated blood vessel zone (1). The incidence rate of ICD among cerebrovascular diseases is ~70% in China (2). It has a serious effect on the health and life of patients, is a burden to the family and society, and inflicts substantial social and economic costs (3).…”
Section: Introductionmentioning
confidence: 99%
“…The protein encoded by CD24 is a small, heavily glycosylated mucin-like cell surface protein [30]. Accumulating evidences had demonstrated that CD24 was involved in epithelial-mesenchymal transition (EMT) and its increased expression was correlated with poor prognosis in patients of epithelial ovarian cancer [31,32]. EPCAM, which encodes an epithelia cell localized type I transmembrane glycoprotein, was initially identi ed as a tumor-associated antigen, which highly expressed in ovarian cancer [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of relapse, it is important to evaluate the impact of CSCs because even patients who demonstrate a positive response to chemotherapy could relapse if a small population of CSCs were to persist [15] . Research has linked the presence of CSCs to chemoresistance and recurrence in OC based on the expression of stem cell markers such as CD24, CD44, CD117, CD133 and aldehyde dehydrogenase (ALDH) [3,13,[16][17][18][19][20][21] . These findings reinforce the importance of CSC markers as biomarkers for the progression of OC [ Table 1].…”
Section: The Onset Of Ovarian Cancer Recurrence and Cancer Stem Cellsmentioning
confidence: 99%